Cardiovascular changes in newly detected hypothyroid patients in Eastern India - Behera, Bijaya Kumar; Satpathy, Anurag; Samal, Karunakar (International Journal of Research in Medical Sciences, 2017)
Background: Present study was carried out with an objective to study all the cardiovascular changes associated with newly detected hypothyroidism, and to know the cardiovascular involvement in sub-clinical hypothyroidism. Methods: A total number of 60 newly detected hypothyroid patients, diagnosed by clinical evaluation and confirmed by thyroid hormone assay by chemiluminescence immunoassay (CLIA) method, were subjected to cardiovascular examination, electrocardiograph, echocardiography and Tread mill test. It was cross sectional study design based on random sampling method which was conducted for 2 years in the department of General Medicine, MKCG Medical College Hospital, Berhampur, Odisha, India. The work was carried out after approval from the Institutional Ethics Committee of MKCG Medical College Hospital, Berhampur, Odisha. Patients were investigated before thyroid hormone replacement therapy. Statistical data analysis was made on basis of deviation, standard error, t-test and the proportion test. P value of < 0.05 was considered statistically significant. Results: Out of 60 patients studied 14 were males and 46 were females. Hypothyroidism was newly diagnosed more in females and maximum in age group of 17-47 years (69.9%). Out of 60 patients, 63.3% had symptoms less than 3 months duration. Cardiovascular symptoms were present in 12 (20%) patients. Bradycardia was observed in 7% patients. Stage 1 hypertension was noticed in 13.3% (diastolic high blood pressure). Low voltage complexes in electrocardiogram was present in 40% study group. Pericardial effusion was present in 26.7% patients. Tread mill test was positive for inducible ischaemia in 2 patients. Diastolic dysfunction was noticed in 26.6% study group. Altered lipid profile was present in 16.7% (S. cholesterol) and 53.4% (S. Triglycerides). Conclusions: Hypothyroidism is common in female, maximum between 17-47 years age group. Majority of the patients did not have any cardiovascular changes. Observed cardiovascular changes were ECG abnormalities, pericardial effusion, diastolic hypertension and diastolic dysfunction. Systematic study was done to know the early effects of hypothyroidism on cardiovascular system. The identification of patients with hypothyroidism is an important individual as well as public health issue. Hence, early detection and initiation of hormone replacement therapy can minimize associated cardiovascular changes.